Response of Benthic Foraminifera to organic matter quantity and quality and bioavailable concentrations of metals in Aveiro Lagoon (Portugal) - Martins, Maria Helena (2015)
This work analyses the distribution of living benthic foraminiferal assemblages of surface sediments in different intertidal areas of Ria de Aveiro (Portugal), a polihaline and anthropized coastal lagoon. The relationships among foraminiferal assemblages in association with environmental parameters (temperature, salinity, Eh and pH), grain size, the quantity and quality of organic matter (enrichment in carbohydrates, proteins and lipids), pollution caused by metals, and mineralogical data are studied in an attempt to identify indicators of adaptability to environmental stress. In particular, concentrations of selected metals in the surficial sediment are investigated to assess environmental pollution levels that are further synthetically parameterised by the Pollution Load Index (PLI). The PLI variations allowed the identification of five main polluted areas. Concentrations of metals were also analysed in three extracted phases to evaluate their possible mobility, bioavailability and toxicity in the surficial sediment. Polluted sediment in the form of both organic matter and metals can be found in the most confined zones. Whereas enrichment in organic matter and related biopolymers causes an increase in foraminifera density, pollution by metals leads to a decline in foraminiferal abundance and diversity in those zones. The first situation may be justified by the existence of opportunistic species (with high reproduction rate) that can live in low oxic conditions. The second is explained by the sensitivity of some species to pressure caused by metals. The quality of the organic matter found in these places and the option of a different food source should also explain the tolerance of several species to pollution caused by metals, despite their low reproductive rate in the most polluted areas. In this study, species that are sensitive and tolerant to organic matter and metal enrichment are identified, as is the differential sensitivity/tolerance of some species to metals enrichment.